PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM ORGANISASI TERHADAP KINERJA MELALUI PENINGKATAN LOYALITAS TENAGA KEPENDIDIKAN - Rahayu, Asti; Chalimah; Gunaedi, Iwan (LPPM Universitas Pekalongan, 2025)
This study aims to analyze the influence of transformational leadership and organizational climate on the performance of education personnel, focusing on the role of loyalty as a mediating variable. The research method used was a survey through a questionnaire of 30 education personnel who were randomly sampling, while the data analysis used SEM-PLS which was processed using the Smart PLS application. The results of the study show that: 1) transformational leadership variables have a positive and significant effect on the performance of education personnel, 2) organizational climate variables have a positive and significant effect on the performance of education personnel, 3) transformational leadership has a positive but insignificant effect on loyalty, 4) organizational climate shows a positive and significant influence on loyalty, 5) employee loyalty has a negative and significant effect on performance, 6) transformational leadership and organizational climate have a direct effect on employee performance, and 7) loyalty does not play a role in mediating the relationship between transformational leadership and organizational climate on performance. Keywords: transformational leadership, organizational climate, loyalty, performance.